Waterborne parasite contamination and risk factors in natural water sources of Karen communities, Omkoi District, Thailand - KULCHANA WONGTHONGLUA; JINTANA YANOLA; SANGOB SANIT; NATTHARINEE KONGTA; WOOTTICHAI NACHAIWIENG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Wongthonglua K, Yanola J, Sanit S, Kongta N, Nachaiwieng W. 2025. Waterborne parasite contamination and risk factors in natural water sources of Karen communities, Omkoi District, Thailand. Biodiversitas 26: 5955-5963. The Karen hill tribes in Omkoi District, Chiang Mai Province, Thailand, continue to experience a high burden of intestinal parasitic infections, likely linked to the use of untreated mountain water for daily consumption. This study investigated protozoan contamination in natural water sources and identified physicochemical factors associated with contamination risk. Water samples were collected from 30 natural sources during the dry (30 samples) and wet seasons (28 samples), totaling 58 samples. Each 20 L sample was filtered, concentrated, and examined using flotation, microscopy, nested PCR to detect Entamoeba histolytica and Entamoeba coli, and the addition of DNA sequencing to detect Giardia duodenalis and Cryptosporidium spp.. Physicochemical parameters, including pH, turbidity, total dissolved solids (TDS), dissolved oxygen, ammonia, chlorine, nitrate, and nitrite, were also measured. Fisher’s exact tests and logistic regression were applied to evaluate associations with contamination. To our knowledge, this study represents the first molecular assessment of protozoan parasites in Omkoi community water sources. E. histolytica was detected in two sources per season (6.67% dry; 7.14% wet), and E. coli in one source per season (3.33% dry; 3.57% wet). G. duodenalis and Cryptosporidium spp. were not detected. Significant associations were observed between contamination and elevated TDS (?200 mg/L; OR = 29.33; 95% CI = 2.08-423.66), ammonia (?0.5 mg/L; OR = 25.50; 95% CI = 1.88-345.83), and nitrite (>0.1 mg/L; OR = 51.00; 95% CI = 4.00-649.10) (P<0.05). Although these parameters are not visually detectable, green algal blooms may indicate nutrient-rich conditions conducive to contamination. In conclusion, routine water treatment, such as boiling or filtration, is recommended before consumption. Residents should avoid water sources with visible algal growth to reduce the risk of protozoan infection in these rural communities.